Using network science to understand the link between subjects and professions. (May 2020) - Haneef, Farah; Abbasi, Rabeeh Ayaz; Sindhu, Muddassar Azam; Khattak, Akmal Saeed; Noor, Muhammad Nouman; Aljohani, Naif Radi; Daud, Ali; Arafat, Sachi
Abstract: Subjects: studied by people often impact their careers. The relation between education and careers has been well studied by social scientists, however limited research on this relation is available in network science. Network science has emerged as a promising field to understand complex systems. We study the relation between education and careers from a network science perspective. In this research we propose methods from network science to understand the relation between the subjects studied by a person and the impact of these subjects on the career of the person. We model the relation between favorite subjects and careers using a network. The model helps in understanding the positive and negative contributions of certain subjects towards other subjects and careers. The results show that mathematics and English are the two basic subjects that are highly related to most of the professions. The detailed results are of particular significance for people associated with higher education and career development. Highlights: Network science is used to study the relationship between subjects and careers. Two-mode network and its projections are used to get deep insights. Signed networks are used to study positive and negative relationships.